The Korean government and public policies in a Development Nexus - Choi , Jongwon ; Kwon , Huck-ju ; Koo , Min Gyo (Springer, 2020)
Contents: 1. Introduction: The Role of Government in South Korea's Consolidation of Economic and Social Development -- 2. The Changes of Political Environment of Public Policy -- 3. The Changes in The Rationale of Governance -- 4. The Changes of the State and Society Relations -- 5. The Decline of Economic Growth Potentials and Future Development of Korea -- 6. The Evolution of the Korean Welfare State in Response to the Societal Change -- 7. Policy Responses to New International Economic Environment in the Post-Uruguay Round Period -- 8. Foreign Policy Challenges and Government Responses -- 9. Summary and Conclusion.